Marathon Events and Its Contribution to the Sports Culture in Hami City, China - liu, tian (Pacific International Journal, 2024)
This study investigates the contribution of marathon events on the sports culture of Hami City, Xinjiang, China. Hami City has recently focused on comprehensive health and fitness strategies, contributing to increased sports participation and competitive achievements. While marathons globally have evolved into events fostering community engagement, healthy lifestyles, and economic growth, their specific contribution on Hami City's sports culture remains underexplored. The study employs a quantitative approach, surveying 180 participants to analyze motivations, deterrents, and the perceived contribution of marathons. Results indicate a higher male representation and strong interest among the 26-35 age group. Personal fitness goals and community involvement motivate participation, while lack of interest and time constraints serve as deterrents. The positive contribution of marathons on sports culture, community engagement, and health is evident, emphasizing the need for tailored strategies for inclusivity and targeted promotional campaigns. The study contributes valuable insights for event planning, community development, and policies aimed at enhancing the sports culture and well-being of Hami City residents. This research explores the unique intersection between marathon events and the cultural landscape of Hami City, providing evidence-based recommendations for future initiatives.